(untitled) (Research, Society and Development, 2021)
The aim of this study was to determine the ideal level of manganese (Mn) supplementation for broilers. Two experiments were carried out, one evaluating a chelated source (amino acid) and the other an inorganic source (oxide) that guarantees better performance and bone quality necessary to support the process of growth, handling, transport, and slaughter. The experimental period was from one to 35 days old, where 1260 male broilers of the Cobb® strain were used. The treatments were defined by supplementing 0, 35, 70, 105 mg of Mn / kg of feed in inorganic or chelated form of the mineral. The occurrence of injuries or bone fractures was observed from the birds’ catch to the slaughter line and no incidence of bone injuries was observed. The estimates of the Mn requirement for broilers for the maximum concentration of this micromineral and Ca in the femur were, respectively, 57,36 mg of Mn / kg and 81,07 mg / kg of supplementation in inorganic form. For the chelated Mn supplementation levels, the requirement estimate was 73,13 mg Mn / kg for the maximum Ca concentration in the femur, with no differences for the Mn concentration in that same bone tissue. The other performance parameters and bone quality evaluated showed no differences for both sources studied. Therefore, there is no need to supplement Mn in a diet based on corn and soybean meal for broilers.